Abnormal Cerebellar Development in Autism Spectrum Disorders - van der Heijden, Meike E; Gill, Jason S; Sillitoe, Roy V (Developmental neuroscience, 2021)
Autism spectrum disorders (ASD) comprise a group of heterogeneous neurodevelopmental conditions characterized by impaired social interactions and repetitive behaviors with symptom onset in early infancy. The genetic risks for ASD have long been appreciated: concordance of ASD diagnosis may be as high as 90% for monozygotic twins and 30% for dizygotic twins, and hundreds of mutations in single genes have been associated with ASD. Nevertheless, only 5-30% of ASD cases can be explained by a known genetic cause, suggesting that genetics is not the only factor at play. More recently, several studies reported that up to 40% of infants with cerebellar hemorrhages and lesions are diagnosed with ASD. These hemorrhages are overrepresented in severely premature infants, who are born during a period of highly dynamic cerebellar development that encompasses an approximately 5-fold size expansion, an increase in structural complexity, and remarkable rearrangements of local neural circuits. The incidence of ASD-causing cerebellar hemorrhages during this window supports the hypothesis that abnormal cerebellar development may be a primary risk factor for ASD. However, the links between developmental deficits in the cerebellum and the neurological dysfunctions underlying ASD are not completely understood. Here, we discuss key processes in cerebellar development, what happens to the cerebellar circuit when development is interrupted, and how impaired cerebellar function leads to social and cognitive impairments. We explore a central question: Is cerebellar development important for the generation of the social and cognitive brain or is the cerebellum part of the social and cognitive brain itself?